Floristic Composition, Vegetation Structure, and Diversity of Urban Home Gardens in Makassar, Indonesia - Erona Wafaretta; Riyan Riyadlun Najih; Amaliah Amriani Amran Saru; Muh. Syaiful Akbar (Science Tech Group, 2026)
Urban home gardens play an important role in supporting biodiversity conservation within urban landscapes. However, information on the floristic composition and vegetation structure of urban home gardens in Indonesian cities remains limited. This study assessed plant diversity, vegetation structure, and alpha diversity of urban home gardens in Makassar, South Sulawesi, Indonesia. Field surveys were conducted in 24 home gardens selected using purposive sampling. All plant species were identified and classified into lower, middle, and upper vegetation strata. Species richness, family composition, and diversity indices were subsequently analyzed. A total of 190 plant species belonging to 65 families and 2,527 individuals were recorded. Araceae and Asparagaceae were the most species-rich families. The middle stratum contained the highest proportion of species (42.1%), followed by the upper (29.5%) and lower strata (28.4%). Mean species richness was 12.8 ± 3.6 species per garden, while Shannon–Wiener diversity, Simpson diversity, and evenness indices were 2.0 ± 0.49, 0.80 ± 0.13, and 0.60 ± 0.18, respectively. These findings demonstrate that urban home gardens in Makassar maintain considerable plant diversity and a multi-layered vegetation structure despite ongoing urbanization. Urban home gardens therefore represent important components of urban green infrastructure and biodiversity conservation.